Effect of Chemical Bath Deposition Variables on the Properties of Zinc Sulfide Thin Films: A Review - Arsad A.Z.; Zuhdi A.W.M.; Abdullah S.F.; Chau C.F.; Ghazali A.; Ahmad I.; Abdullah W.S.W. (MDPI, 2024)
Zinc sulfide (ZnS) thin films prepared using the chemical bath deposition (CBD) method have demonstrated great viability in various uses, encompassing photonics, field emission devices, field emitters, sensors, electroluminescence devices, optoelectronic devices, and are crucial as buffer layers of solar cells. These semiconducting thin films for industrial and research applications are popular among researchers. CBD appears attractive due to its simplicity, cost-effectiveness, low energy consumption, low-temperature compatibility, and superior uniformity for large-area deposition. However, numerous parameters influence the CBD mechanism and the quality of the thin films. This study offers a comprehensive review of the impact of various parameters that can affect different properties of ZnS films grown on CBD. This paper provides an extensive review of the film growth and structural and optical properties of ZnS thin films influenced by various parameters, which include complexing agents, the concentration ratio of the reactants, stirring speed, humidity, deposition temperature, deposition time, pH value, precursor types, and annealing temperature environments. Various studies screened the key influences on the CBD parameters concerning the quality of the resulting films. This work will motivate researchers to provide additional insight into the preparation of ZnS thin films using CBD to optimize this deposition method to its fullest potential. 2023 by the authors.